Alfabetização de jovens e adultos: Autonomia dos sujeitos na perspectiva da educação libertadora em Paulo Freire - SOUSA, Polyana dos Santos (2023)
The present dissertation has as its central axis Youth and Adult Literacy: the autonomy of individuals from the perspective of liberating education in Paulo Freire. Its objective is to analyze the literacy process in Youth and Adult Education and its contributions to the development of autonomy and transformation of the learner participants. For the theoretical framework, we presented the historical context of Youth and Adult Education in Brazil, with an emphasis on the 20th century, engaged with literacy approaches, and presented literacy from the Freirean perspective. In the methodological field, we followed the paths of qualitative research and engaged with the categories of totality, contradiction, historicity, and mediation of dialectical historical materialism. The research was guided by the interventionist approach of action research, with eight learner participants in the study. The research site was Mariana Luz Municipal School. For data collection, we used field diaries, recordings, and the implementation of a cultural circle, which allowed us to gather the vocabulary universe and select the generative word. We used collective text to capture recurring issues. To analyze the data, we began with the memories related to literacy that the learners bring to the classroom, and we also presented how the Freirean literacy praxis can contribute to the development of learners' autonomy, sharing participants' accounts and experiences of how literacy grounded in liberating education transformed their lives.